The Influence of Final-Year Students’ Perceptions of Compensation and Work Environment on Interest in Applying for Jobs in Ponorogo - Danik Choiriyah Purnomo; Ely Masykuroh (Niqosiya: Journal of Economics and Business Research, 2026)
Introduction: A factor that causes someone has a interested in applying for a job are needs to fulfill. There are five levels of needs, namely physiological, safety, social, esteem, and self-actualization. The purpose of this study is to determine the influence of compensation and work environment on interest in applying for a job. The relationship between compensation and the work environment with job application interest indicates that both factors play a significant role in attracting prospective job applicants. Adequate compensation reflects the company’s appreciation for employees’ efforts and capabilities, thereby increasing individuals’ interest in applying for a position. Compensation is not limited to salary alone, but also includes allowances, bonuses, incentives, health insurance, and other facilities provided by the company. The more competitive the compensation offered, the greater the individual’s interest in joining the organization. In addition to compensation, the work environment is also a factor that influences job application interest. A comfortable, safe, and conducive work environment, along with positive social relationships, can create a sense of comfort for prospective employees. The work environment encompasses physical conditions such as cleanliness, lighting, and workplace facilities, as well as non-physical conditions such as communication among employees, organizational culture, and supervisory support. Companies with a positive work environment tend to attract greater interest because they are perceived as being able to provide comfort and support employee productivity. This study was conducted among final-year students in Ponorogo, as final-year students are considered to have the readiness to choose their careers after completing their education. This study used a quantitative approach. The population consisted of 4,069 final-year students in Ponorogo, with 98 respondents selected using probability sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results of this study indicate that compensation has a positive and significant influence on interest in applying for jobs. The work environment has a positive and significant influence on interest in applying for jobs. Simultaneously, compensation and the work environment have an influence on interest in applying for jobs.